Isolated nocturnal and isolated daytime hypertension associate with altered cardiovascular morphology and function in children with chronic kidney disease: findings from the Cardiovascular Comorbidity in Children with Chronic Kidney Disease study - Düzova, Ali; Kirchner, Marietta; Schaefer, Franz; Wühl, Elke (Journal of hypertension, 2019)
Introduction: Prevalence of isolated nocturnal hypertension (INH) and isolated daytime hypertension (IDH) is around 10% in adults. Data in children, especially in chronic kidney disease (CKD), are lacking. The aim of this cross-sectional multicenter cohort study was to define the prevalence of INH and IDH and its association with cardiovascular morphology and function, that is, pulse wave velocity (PWV), carotid intima-media thickness (cIMT), or left ventricular mass index (LVMI) in children with CKD. Methods: Ambulatory blood pressure (BP) monitoring profiles were analyzed in 456 children with CKD stages III-V participating in the Cardiovascular Comorbidity in Children with Chronic Kidney Disease Study (64.3% males, 71.3% congenital anomaly of the kidney and urinary tract, age 12.5 ± 3.2 years, estimated glomerular filtration rate 29 ± 12 ml/min per 1.73 m2). Baseline PWV, cIMT, and LVMI were compared in normotension, INH, IDH, or sustained 24-h hypertension. Results: Prevalence of sustained hypertension was 18.4%, of INH 13.4%, and of IDH 3.7%. PWV SDS (SD score) and cIMT SDS were significantly higher in sustained hypertension and INH, and PWV SDS was significantly higher in IDH, compared with normotension. LVMI was significantly increased in sustained hypertension, but not in INH or IDH. Determinants of INH were smallness for gestational age, older age, higher height SDS and parathyroid hormone, and shorter duration of CKD. In logistic regression analysis, day/night-time hypertension or ambulatory BP monitoring pattern (normal, INH, IDH, sustained hypertension) were independently associated with cardiovascular outcome measures: elevated night-time BP was associated with increased cIMT, PWV, and left ventricular hypertrophy; INH was associated with cIMT. Conclusion: INH is present in almost one out of seven children with predialysis CKD; INH and nocturnal hypertension in general are associated with alterations of arterial morphology and function.